Do Textbooks Really Promote Gender Equality?: A Multimodal Analysis of Gender Roles - Asriyama, Weksa Fradita; Sari, Eka Dyah Puspita (English Language Education, Universitas Internasional Batam, 2022)
Gender equality has been promoted by UNICEF since 1995. One strategical way to promote gender equality is through education by exposing the youth to nonbiased learning materials. This paper investigates the representation of gender roles in two English textbooks for senior high school students. Gender related images and texts are taken as the data. The data were analysed using Bruggeilles and Cromer’s (2009) framework for gender typical roles. Findings reveal that in both textbooks, males have the roles as leaders in domestic, social, and occupational sphere while females are considered as keepers, protectors, and caretakers in those spheres.